Yesterday [videorecording (DVD)] - Patel, Himesh, 1990-; James, Lily, 1989-; Fry, Joel; Sheeran, Ed, 1991-; McKinnon, Kate, 1984-; Bhaskar, Sanjeev, 1964-; Syal, Meera (Universal Pictures Home Entertainment, 2019)
Jack Malik was just another struggling songwriter... but that was yesterday. After a mysterious blackout, Jack discovers he is the only person on earth who remembers The Beatles! As he rockets to fame by passing off the Fab Four's songs as his own, Jack risks losing Ellie--the one person who has loved him and believed in him from the start. Before the door to his old life closes forever, Jack must decide if all he needs is love, after all.